Evaluation of antihistaminic activity of quercetin by using histamine induced bronchospasm and clonidine induced catalepsy models - H., Ramesh; Nadaf, Reshma (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Histamine is an important mediator of allergic reactions. Even though presently available antihistaminics are effective in treatment of allergic reactions, still there is scope for better new drugs. Quercetin has been used as a nutritional supplement and may be beneficial against a variety of diseases. Some of the beneficial effects include anticancer, antitumor, anti-ulcer, anti-allergy and anti-inflammatory effects. As quercetin is used in traditional system of medicine for treatment of allergies, this study was undertaken to evaluate antihistaminic activity of quercetin. Methods: In histamine induced bronchospasm model, 18 guinea pigs were divided into 3 groups. Control group received normal saline, standard control group received Chlorpheniramine and test group received Quercetin. All drugs were given once daily for 5 days. Preconvulsive dyspnoea was calculated on day 0 and day 5 for all guinea pigs after administration of Histamine aerosol. In clonidine induced catalepsy model, 18 albino mice were divided into 3 groups. Control group, standard control group and test group received normal saline, Chlorpheniramine and Quercetin respectively. One hour after administration of drugs the mice were given clonidine and catalepsy was measured at 30, 60, 90, 120 and 150 min. Results: In histamine induced bronchospasm model, both chlorpheniramine and quercetin produced significant protection as compared to control group. In clonidine induced catalepsy model the effect of quercetin was comparable to chlorpheniramine. Conclusions: Quercetin has significant antihistaminic activity. It appears to be due to H1 receptor blockade, contrary to the belief that it inhibits release of histamine from mast cells.